Effect of Smoking Reduction on Birth Weight: Benefits of Temporarily Quitting Smoking and Smoking Less - Zhen-Qiang Ma; Monica A Fisher (Archives of Preventive Medicine - Peertechz Publications, 2016)
Objectives: To assess the benefits of smoking cessation beyond measuring success as completely quitting smoking. To consider time-specific and dose-dependent smoking cessation as important harm reduction measures during pregnancy. Methods: Cross-sectional study quantified the independent effects of a longitudinal-type measure of maternal smoking prior to, and during pregnancy on baby's birth weight, using Pennsylvania 2011 birth certificates data on 90,702 live singleton term births. Multivariate linear regression modeling was performed. Results: Maternal smoking status: Among the 22% of mothers who smoked pre-pregnancy, during pregnancy 53% continued to smoke throughout, 28% completely quit, and 18% partially quit. Adjusted birth weight: Compared to babies born to non-smokers, on average, mothers who: 1) Smoked pre-pregnancy and during all trimesters had the lowest birth weight babies (166g less). 2) Didn't smoke pre-pregnancy but smoked during pregnancy had the second lowest birth weight babies (133g less). 3) Smoked prepregnancy but partially quit during pregnancy had the third lowest birth weight babies (66g less). 4) Smoked pre-pregnancy but completely quit during pregnancy had babies with similar birth weights. 5) Mothers who self-designated as Black race had babies weighing 148 g less. Birth weights were 5g less for every cigarette smoked/day during the last trimester.